A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia - García, Juan C.; Lynch, John D. (Zootaxa, 2006)
A new species of the genus Eleutherodactylus (Leptodactylidae) is described from a cloud forest in western Departamento del Cauca, in Munchique National Park, sector La Romelia, between 2550 and 2750 m., and E. hectus is verified for the region.